Relative age effect on behavioural regulation, burnout potential and anxiety of sports students - Peter O'Donoghue; Richard Neil (European Journal of Human Movement, 2015)
Introduction: Relative age effect in sport is widely recognised due to the volume of research that has found a greater tendency for late born people within cohorts to dropout of sport before becoming adults than for early born people. However, most of the studies in relative age report on broad participation rates of people born at different times of the year. There is little research into potential psychological effects of relative age. Comparing early and late born people using psychological variables could provide valuable information about the mechanisms of dropout. Therefore, the purpose of the current investigation was to compare early and late born university sports students using the Sport Anxiety Scale-2 (SAS-2), the Behavioural Regulation in Sport Questionnaire (BRSQ) and the Athlete Burnout Questionnaire (ABQ).  Early born participants were those born in the first 6 months of the academic year (September to February) and late born participants were born in the second half (March to August).  Gender, size of place of birth  and type of sport were also included as independent variables within the study. Materials and Methods: There were 222 students who participated in the study including 119 males and 103 females. Results: There were no significant differences between the early born and late born students for any of the psychological variables measured. There were also no significant interaction effects of half year of birth and any combination of gender, size of birthplace or type of sport on any of the psychological variables. Discussion: Efforts to model pathways for psychological variables based on month of birth cannot be justified based on the findings of the current descriptive study.